The Impact of Science Workstation Strategy on Enhancing Student Engagement in Science Classes - Caylan, Angelyn T.; Canonio, Alle Mediha C.; Baluyos, Genelyn R. (PT ARRUS Intelektual Indonesia, 2025)
Student engagement stands as a critical determinant of academic success and learning outcomes, particularly in the realm of science education, where active participation and enthusiasm significantly impact knowledge acquisition and retention. This study aimed to enhance the engagement of Grade 7 students in science classes using the Science Workstation Strategy in one of the public schools in Ozamiz City during the academic year 2023-2024. The study utilized a classroom-based action research design. Thirty - five participants were selected through purposive sampling during the A.Y. 2023-2024 in a public school in Ozamiz City. The study used a researcher-made test and Minitab statistical software, utilizing tools such as mean, standard deviation, and t-test. The study yielded the following findings: (1) On the average, students’ engagement displayed a high level of engagement before using the workstation strategy; (2) The students’ engagement after using the Science Workstation Strategy improved significantly. They performed within the Moderately High range; (3) There was a significant difference in students’ engagement before and after using the Science Workstation Strategy; and (4) There are other observed improvements among the students after the use of the Science Workstation Strategy. In conclusion, using the science workstation strategy effectively improved students’ engagement in science and enhance learning experiences. This supports a recommendation in adopting this strategy as teaching method to improve student engagement in science classes.